Educating for peace for authentic growth and different conflict management - Gennaro Balzano (Firenze University Press, 2024)
Peace education is a central issue when we speak of authentic child development. Of all educations (the most transversal), it relates both to forming citizens who always defend this idea and at all costs, and to the prospect of women and men practicing peace, in the broadest sense, daily. One way to do this is to start from the school and from those activities capable of proposing a different management of conflict. The example cited at the conclusion of this work is, after a specific activity, the community discussion and, therefore, the way of the word. Even though, in the wake of the Russian-Ukrainian and Israeli-Palestinian conflicts, schools have engaged in very varied but nevertheless time-limited projects, it is important to emphasize that everyday disciplinary activities are not enough, just as it is not enough to relegate this topic, in primary school, to civic education hours.   Educare alla pace per una crescita autentica e una diversa gestione dei conflitti. L'educazione alla pace è questione centrale quando parliamo di sviluppo autentico del bambino. Tra le educazioni (la più trasversale) afferisce sia al formare cittadini che difendano sempre e ad ogni costo tale idea, sia al prospettare che donne e uomini pratichino la pace, in senso ampio, quotidianamente. Una via per far questo è ripartire dalla scuola e da quelle attività in grado di proporre una diversa gestione del conflitto. L'esempio, citato a conclusione di tale lavoro è, dopo una precisa attività, la discussione comunitaria e, dunque, la via della parola. Nonostante, a seguito dei conflitti russo-ucraino e israelo-palestinese, le scuole si siano cimentate in progettualità molto variegate ma tuttavia a tempo determinato, preme sottolineare come le quotidiane attività disciplinari non bastino, così come non basta relegare tale tema, nella scuola primaria, alle ore di educazione civica.